Premolarized double dens in dente in albinism - A case report - Suprabha B (Wolters Kluwer Medknow Publications, 2005)
Dens in dente are known to be associated with many dental abnormalities such as taurodontism microdontia, gemination, and dens evaginatus. This paper describes a rare case of double dens in dente in a lateral incisor with crown morphology similar to a premolar present in a patient with features of albinism. Problems associated with this condition and their management is discussed.